磁致伸缩材料在高频驱动时内部磁场强度的分布及其对磁致伸缩性能的影响 - 汪建新; 高耀东; 任冲翀 (Jixie Chuandong, 2007)
It is analysed that the distribution of the magnetic field inside a cylindrical shaped Terfenol-D material bar at its working condition by Maxwell’s equations,some problems that may be occured under high working frequency is pointed out.The result is very useful to make use of the Terfenol-D material reasonable.Meanwhile,an idea used to calculate the magnitude of magnetic field at boundary surface of Terfenol-D material bar is discussed also.